Effect of different sodium nitrate concentrations on the growth, biomass, and biochemical composition of Tetraselmis chuii - Fakhri, Muhammad; Amrulloh, Albazi Achmad; Yuniarti, Ating; Supriatin, Febriyani Eka; Arifin, Nasrullah Bai (Journal of Aquaculture and Fish Health, 2025)
Nitrogen plays a significant role in the growth and metabolism of microalgae. The purpose of this study was to investigate the influences of different sodium nitrate concentrations on growth, biomass, and biochemical profile in Tetraselmis chuii. Four different nitrate concentrations, 0.5, 1.0, 1.5, and 2.0 g/L NaNO3 were applied in T. chuii culture under a batch system. It was found that a low nitrate concentration of 0.5 g/L NaNO3 produced the highest specific growth rate and biomass concentration of T. chuii. On the other hand, increasing nitrate concentration led to an increase in chlorophyll a+b and carotenoid in T. chuii, with the optimum nitrate concentration found at 1.5 g/L NaNO3. Under the nitrogen limitation condition, protein content was significantly decreased, but lipid and carbohydrate content were highly accumulated in the cells. This study provides a unique phenomenon that low nitrogen concentrations not only produce higher biomass but also accumulate high lipid and carbohydrate content.